A Real Time Implementation of TBMAC using IEEE 802.11b - Gleeson, Mark (Trinity College Dublin. Department of Computer Science, 2004)
Emergency services, and automated vehicle platoons are frequently used examples of the need for real-time ad hoc communication, which demand that communication be time bounded overall. The medium access control protocol regulates access to the medium. Time division protocols give deterministic, time bounded delivery of messages. TDMA, time division multiple access forms the basis of the time bounded medium access control protocol, TBMAC. TBMAC provides every mobile station with predictable access to the medium with known probability and bounded delay. Currently TBMAC has been simulated using the NS2 simulator. This dissertation implements TBMAC using RTAI real-time Linux and IEEE 802.11b as a basis. The implementation supports a non empty cell with a static cell membership. The implementation makes use of the broadcast tightness property to achieve tight clock synchronisation between multiple stations. The TBMAC protocol was implemented in real-time using the TDMA MAC layer during the dissertation. Simulations have been relied upon in the evaluation of new MAC protocols. This dissertation evaluates the TBMAC protocol in the real world and compares its performance to that of the CSMA MAC protocol. Real world experiments give a much better and more realistic view of the performance of the MAC protocol compared to experiments carried out in a simulator.
Keywords: Computer Science